Metagenomic characterization of the antibiotic, biocide, and metal resistome of soil and romaine lettuce from the field through processing and storage - Susan R. Leonard; Mark K. Mammel; Taylor K.S. Richter; Ivan Simko; Maria T. Brandl (International Journal of Food Microbiology, 2026)

Foliar Application of Silicon Dioxide Improves Lettuce Growth Parameters, Disease Resistance, Post-Harvest Quality, and Modifies Mineral Composition - Ivan Simko; Hui Peng; Daniel K. Hasegawa (Journal of Soil Science and Plant Nutrition, 2026)
Purpose This study investigated foliar-applied silicon dioxide (SiO 2 ​), alone and with calcium (Ca), as a sustainable strategy to enhance lettuce quality and performance, using a genetically diverse panel of accessions for broad applicability. Methods We conducted multi-year outdoor pot and field experiments to assess the effects of a range of SiO 2 ​ and Ca concentrations and a promising subset of treatments, respectively. We evaluated key horticultural traits, resistance to diseases, pests, and physiological disorders, as well as post-harvest quality and plant mineral composition. Results The treatments provided significant benefits for several quality-related traits. A combination of 3.66 mM SiO 2 and 2.50 mM Ca significantly improved plant biomass, leaf thickness, and anthocyanin concentration in pot experiments. In field trials, 3.66 mM SiO 2 ​ application delayed bolting, reduced downy mildew severity, and increased leaf thickness, chlorophyll, and anthocyanin content. Notably, the combined SiO 2 and Ca spray significantly reduced post-harvest deterioration in both pot and field experiments, demonstrating a synergistic interaction. Analysis of mineral elements revealed that the treatments modified the uptake and correlations among several elements in the plant tissue. Conclusion Foliar SiO 2 ​ and Ca applications, particularly in combination, represent an effective approach for enhancing key lettuce quality parameters. While no significant yield gains were observed in field trials, the improvements in post-harvest quality, disease resistance, delayed bolting, and plant composition are clear evidence that this strategy can reduce crop losses and improve overall product quality.

A major and stable QTL confers impatiens necrotic spot virus resistance in lettuce cv. Eruption - Santosh Nayak; Kelley L. Richardson; Renée L. Eriksen; Daniel K. Hasegawa; William M. Wintermantel; Manoj Sapkota; Xuemei Tang; Shufen Chen; Meng Lin; Dongyan Zhao; Craig T. Beil; Moira J. Sheehan; et al. (Theoretical and Applied Genetics, 2025)
Key message A large effect and environmentally stable QTL was identified on LG2 that confers high levels of INSV resistance in lettuce cultivar Eruption. Abstract Impatiens necrotic spot virus (INSV) has recently emerged as a major threat to lettuce production in the Salinas Valley of California, the region which contributes over 60% of the US national supply. This thrips-transmitted virus can infect lettuce plants at any growth stage, causing premature death or a total loss of marketability. Both INSV and its thrips vector have broad host ranges, which complicate disease management. Utilizing genetic resistance is the most sustainable approach; however, complete immunity has not been identified and the genetic basis of resistance to INSV in lettuce remains poorly understood. This study aimed to identify quantitative trait loci (QTL) and elucidate the underlying mechanism of INSV resistance in ‘Eruption,’ a lettuce cultivar exhibiting highly stable partial resistance across environments. Using 162 F 6:8 recombinant inbred lines (RILs) developed from a cross between moderately susceptible ‘Reine des Glaces’ and ‘Eruption,’ and a genetic linkage map comprising 1598 single nucleotide polymorphism (SNP) markers, phenotypic data collected from field and greenhouse experiments consistently revealed a highly significant, major QTL on linkage group 2. This QTL exhibited partial dominance with additive effects, explaining up to 61% of the total phenotypic variation for INSV disease severity. Furthermore, INSV resistance was found to be highly heritable, with heritability estimates of up to 0.89, indicating strong genetic control. Results of this study are crucial for fine mapping and the development of marker-assisted selection assays to accelerate the breeding of more advanced INSV-resistant lettuce cultivars.

Unraveling the variation, phylogeny, and taxonomy of Lactuca spp. for germplasm management and breeding - Aleš Lebeda; Ľuboš Majeský; Eva Křístková; David C. A. Pink; Ivan Simko (Planta, 2025)

Differential low oxygen response and transcriptomic shifts drive fresh-cut lettuce deterioration in modified atmosphere packaging - Hui Peng; Dean O. Lavelle; Maria Jose Truco; Richard W. Michelmore; Ivan Simko (Postharvest Biology and Technology, 2025)

Escherichia coli O157:H7 multiplication in the latex of diverse lettuce genotypes is negatively correlated with plant peroxidase activity - Andree S. George; Ivan Simko; Maria T. Brandl (International Journal of Food Microbiology, 2025)

Identification and characterization of lettuce cultivars with high inhibitory activity against the human pathogen Escherichia coli O157:H7: Toward a plant-intrinsic hurdle approach to microbial safety - Andree S. George; Ivan Simko; Maria T. Brandl (Postharvest Biology and Technology, 2024)

Genome-wide association mapping reveals loci for enzymatic discoloration on cut lettuce - Hui Peng; Yaguang Luo; Zi Teng; Bin Zhou; Daniel Pearlstein; Dongyi Wang; Ellen Turner; Xiangwu Nou; Thomas T.Y. Wang; Yang Tao; Jorge M. Fonseca; Ivan Simko (Postharvest Biology and Technology, 2024)

Genetic determinants of lettuce resistance to drop caused by Sclerotinia minor identified through genome-wide association mapping frequently co-locate with loci regulating anthocyanin content - Ivan Simko; Jinita Sthapit Kandel; Hui Peng; Rebecca Zhao; Krishna V. Subbarao (Theoretical and Applied Genetics, 2023)

Weather factors, soil microbiome, and bacteria-fungi interactions as drivers of the epiphytic phyllosphere communities of romaine lettuce - Maria T. Brandl; Mark K. Mammel; Ivan Simko; Taylor K.S. Richter; Solomon T. Gebru; Susan R. Leonard (Food Microbiology, 2023)

Genome-wide association mapping reveals genomic regions frequently associated with lettuce field resistance to downy mildew - Ivan Simko; Hui Peng; Jinita Sthapit Kandel; Rebecca Zhao (Theoretical and Applied Genetics, 2022)

Correction to: Lettuce (Lactuca sativa L.) germplasm resistant to bacterial leaf spot caused by race 1 of Xanthomonas hortorum pv. vitians (Brown 1918) Morinière et al. 2020 - Germán V. Sandoya; Emma Rosenthal; Ivan Simko; Lis N. Rodrigues-Porto; William H. Wadlington; Carolee T. Bull; Amanda Carroll (Journal of Plant Pathology, 2022)

Lettuce (Lactuca sativa L.) germplasm resistant to bacterial leaf spot caused by race 1 of Xanthomonas hortorum pv. vitians (Brown 1918) Morinière et al. 2020 - Germán V. Sandoya; Emma Rosenthal; Ivan Simko; Lis N. Rodrigues-Porto; William H. Wadlington; Carolee T. Bull; Amanda Carroll (Journal of Plant Pathology, 2022)

Mapping and identification of genetic loci affecting earliness of bolting and flowering in lettuce - Leah Rosental; David W. Still; Youngsook You; Ryan J. Hayes; Ivan Simko (Theoretical and Applied Genetics, 2021)

Genome-wide association mapping reveals loci for shelf life and developmental rate of lettuce - Jinita Sthapit Kandel; Hui Peng; Ryan J. Hayes; Beiquan Mou; Ivan Simko (Theoretical and Applied Genetics, 2020)

The genetics of resistance to lettuce drop (Sclerotinia spp.) in lettuce in a recombinant inbred line population from Reine des Glaces × Eruption - Bullo Erena Mamo; Ryan J. Hayes; Maria José Truco; Krishna D. Puri; Richard W. Michelmore; Krishna V. Subbarao; Ivan Simko (Theoretical and Applied Genetics, 2019)

Maturity-Adjusted Resistance of Potato (Solanum tuberosum L.) Cultivars to Verticillium Wilt Caused by Verticillium dahliae - Ivan Simko; Kathleen G. Haynes (American Journal of Potato Research, 2017)

Mapping a dominant negative mutation for triforine sensitivity in lettuce and its use as a selectable marker for detecting hybrids - Ivan Simko; Ryan J. Hayes; María José Truco; Richard W. Michelmore (Euphytica, 2011)

Quantitative resistance to late blight from Solanum berthaultii cosegregates with R Pi-ber : insights in stability through isolates and environment - Gilda Rauscher; Ivan Simko; Hilary Mayton; Merideth Bonierbale; Christine D. Smart; Niklaus J. Grünwald; Andrew Greenland; William E. Fry (Theoretical and Applied Genetics, 2010)

Mapping loci for chlorosis associated with chlorophyll b deficiency in potato - Ivan Simko; Jan H. van den Berg; Dick Vreugdenhil; Elmer E. Ewing (Euphytica, 2008)

Comparative analysis of quantitative trait loci for foliage resistance toPhytophthora infestans in tuber-bearingSolanum species - Ivan Simko (American Journal of Potato Research, 2002)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)